2010
DOI: 10.1037/a0020637
|View full text |Cite
|
Sign up to set email alerts
|

Provider role attitudes, marital satisfaction, role overload, and housework: A dyadic approach.

Abstract: Treating the marital dyad as the unit of analysis, this study examined the within-couple patterning of 272 dual-earner spouses' provider role attitudes and their longitudinal associations with marital satisfaction, role overload, and the division of housework. Based on the congruence of husbands' and wives' provider role attitudes, couples were classified into one of four types: (1) main-secondary, (2) coprovider, (3) ambivalent coprovider, and (4) mismatched couples. Nearly half of all spouses differed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…Being overloaded at work may not necessarily lead to marital arguments, as managers may view the WFC as a price to pay to achieve success (Bagger and Li, 2012). Another explanation for the non-significant effect might be that dual-career couples report a more equitable division of household work and higher marital satisfaction than single-career couples (Helms et al, 2010). Finally, while time-based FWC was found to exacerbate managers' career satisfaction, the opposite was found relative to strain-based FWC.…”
Section: Discussionmentioning
confidence: 87%
“…Being overloaded at work may not necessarily lead to marital arguments, as managers may view the WFC as a price to pay to achieve success (Bagger and Li, 2012). Another explanation for the non-significant effect might be that dual-career couples report a more equitable division of household work and higher marital satisfaction than single-career couples (Helms et al, 2010). Finally, while time-based FWC was found to exacerbate managers' career satisfaction, the opposite was found relative to strain-based FWC.…”
Section: Discussionmentioning
confidence: 87%
“…Peplau suggested that such discrepancies are more strongly linked to husbands' marital satisfaction than to wives' marital satisfaction, particularly when the role behavior under consideration is wives' employment. Although not always achieved, Peplau and others have suggested that consistency between role ideals and behavior, as well as withincouple consensus about roles, is optimal for marital satisfaction (Helms, Walls, Crouter, & McHale, 2010).…”
Section: A Theoretical Model Of Gender Roles In Marriagementioning
confidence: 99%
“…This finding may be further explained by the meaning spouses ascribe to wives' employment-a factor not examined in the current study. The perceived necessity of wives' employment, husbands' support of wives' employment, spouses' decision-making strategies about wives' employment, spouses' internalized provider-role ideologies, and husbands' attitudinal flexibility to manage changing role behavior demands (Bean et al, 1977;Chavira-Prado, 1992;Fernandez Kelly, 1992;Grzywacz et al, 2009;Helms et al, 2010;Menjivar, 1999) may be particularly important in understanding Mexican-origin husbands' marital satisfaction in the context of both spouses' gender role attitudes and wives' employment.…”
Section: Spouses' Individual Characteristics and Husbands' Marital Samentioning
confidence: 99%
See 1 more Smart Citation
“…If multiple models based on different variables are to be estimated, for example, a complete-case approach may result in different, albeit possibly overlapping, samples (e.g., Helms, Walls, Crouter, & McHale, 2010). This can make comparisons among different models difficult and statistical inference complicated if data are not MCAR.…”
Section: Data Analysis With Missing Datamentioning
confidence: 99%